Administrative problems in metropolitan areas : a case study of Pimpri-Chinchwad municipal area - Prabhavalkar, B. H. (Regional Centre for Training and Research in Municipal Administration of All-India Institute of Local Self-Government, 1977)
On the problems of urban development in the Poona metropolitan area.